Modified technique for esthetic crown lengthening in the natural dentition: case series - Lobo, Maristela; Monteiro, Mabelle F.; Rodrigues, Rachel Q. F.; Xambre, Pedro A. O.; Rondina, Adriana R.; Andere, Naira M. R. B. [UNESP]; Santos, Nidia C. Castro dos (Quintessence Publishing Co Inc, 2022)
Aim: The objective of the present case series was to propose a modified technique for esthetic crown lengthening surgery (ECLS) and a new method for categorizing esthetic parameters in terms of the gingival tissue as well as to assess treatment outcomes after 6 months. Materials and methods: Patients seeking ECLS were enrolled according to inclusion and exclusion criteria that are decribed in the materials and methods criteria. Digital photographs were obtained at baseline and at 6 months postsurgery. Soft tissue cone beam computed tomography (ST-CBCT) was performed at baseline, and the dimensions of the periodontal tissue were digitally measured. All patients were submitted to the modified ECLS. Periodontal esthetic outcomes were evaluated according to the crown lengthening esthetic score (CLES) system. The mean CLES and its subdomains (gingival zenith [GZ], papillae, and gingival recession [GR]) were compared at baseline and 6 months using the paired t test and the Wilcoxon signed-rank test. Results: Fifteen patients were assessed. At 6 months, the mean CLES (15.23 +/- 2.49 to 20.30 +/- 2.65), GZ (4.80 +/- 1.17 to 7.28 +/- 1.97), and papillae (4.62 +/- 2.30 to 7.30 +/- 0.95) presented statistically significant differences compared with baseline. GR did not present significant changes at 6 months. Conclusions: The modified ECLS technique effectively improved esthetic periodontal parameters in the present case series. The CLES system may be a useful tool for assessing ECLS outcomes.